2021
DOI: 10.1038/s41598-020-80390-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effects of prenatal bisphenol A exposure on autism-related genes and their relationships with the hippocampus functions

Abstract: Our recent study has shown that prenatal exposure to bisphenol A (BPA) altered the expression of genes associated with autism spectrum disorder (ASD). In this study, we further investigated the effects of prenatal BPA exposure on ASD-related genes known to regulate neuronal viability, neuritogenesis, and learning/memory, and assessed these functions in the offspring of exposed pregnant rats. We found that prenatal BPA exposure increased neurite length, the number of primary neurites, and the number of neurite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 118 publications
3
50
0
1
Order By: Relevance
“…This is the first study to demonstrate that prenatal BPA exposure, even at the (NOAEL), alters the transcriptome-interactome profiles of genes in the offspring's prefrontal cortex in a sex-dependent manner, possibly through ASD-related transcription factors (Figure 3). This finding is consistent with our previous studies, which observed the sex-specific effects of maternal BPA exposure on the transcriptome-interactome profiles of the offspring hippocampus [15,16,125]. Moreover, Thongkorn et al found that the expression of several ASD candidate genes (e.g., Mief2, Eif3h, Cux1, and Atp8a1) in the hippocampus is dysregulated in response to prenatal BPA exposure and shows a sex-specific correlation with neuronal viability, neuritogenesis, and/or learning/memory [16].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is the first study to demonstrate that prenatal BPA exposure, even at the (NOAEL), alters the transcriptome-interactome profiles of genes in the offspring's prefrontal cortex in a sex-dependent manner, possibly through ASD-related transcription factors (Figure 3). This finding is consistent with our previous studies, which observed the sex-specific effects of maternal BPA exposure on the transcriptome-interactome profiles of the offspring hippocampus [15,16,125]. Moreover, Thongkorn et al found that the expression of several ASD candidate genes (e.g., Mief2, Eif3h, Cux1, and Atp8a1) in the hippocampus is dysregulated in response to prenatal BPA exposure and shows a sex-specific correlation with neuronal viability, neuritogenesis, and/or learning/memory [16].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with our previous studies, which observed the sex-specific effects of maternal BPA exposure on the transcriptome-interactome profiles of the offspring hippocampus [15,16,125]. Moreover, Thongkorn et al found that the expression of several ASD candidate genes (e.g., Mief2, Eif3h, Cux1, and Atp8a1) in the hippocampus is dysregulated in response to prenatal BPA exposure and shows a sex-specific correlation with neuronal viability, neuritogenesis, and/or learning/memory [16]. The neuronal viability and neuronal density in the hippocampus and learning/memory are reduced only in the male offspring, while those in the females are not affected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The rats were given food and RO-UV water ad libitum. These rats were given 5000 µg/kg BW of BPA daily [ 32 , 33 , 34 , 35 ] (Cat. No.…”
Section: Methodsmentioning
confidence: 99%
“…Des études mettent en relation les modifications de comportements observées chez les rongeurs avec des altérations de la régulation épigénétique (en particulier la méthylation de l'ADN) de l'expression de gènes essentiels au fonctionnement neuronal aux étapes précoces (60,65,72,73) et à différents niveaux du cerveau (hippocampe, hypothalamus). Les effets sur le transcriptome et les fonctions cérébrales seraient sexe dépendante (74). Dans la descendance des souris soumises pendant la gestation à une exposition aux perturbateurs endocriniens (BPA, phtalates, pesticides), équivalente à celle d'une cohorte de naissance suédoise, des altérations long terme dans les comportements sont observées avec modification de l'expression de gènes du cerveau.…”
Section: Etudes Expérimentales Modes D'action Et Mécanismesunclassified